Pengaruh Etika Kerja dan Komitmen Organisasional terhadap Kinerja Karyawan BPR Gianyar Parthasedana - Wahyuningsih, Luh Komang; Wijaya, Putu Yudy; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Intense competition in the service industry, especially financial institutions, encourages every financial institution to improve employee performance in order to compete and develop. PT. PT. BPR Gianyar Parthasedana and based on observations found there were problems related to work ethics and organizational commitment. The purpose of this study was to determine the effect of work ethics and organizational commitment on employee performance either partially or simultaneously. This research was conducted at PT. BPR Gianyar Parthasedana with a population of 48 employees. This study uses census techniques so that all members of the population are involved as research subjects. Primary data collection is done by using a questionnaire. Hypothesis testing is done using multiple linear regression. Based on the results of the analysis it can be interpreted that: 1) Work ethics have a positive and significant effect on employee performance, 2) Organizational commitment has a positive and significant effect on employee performance, 3) Work ethics and formational beliefs have a positive and significant effect on employee performance.